3D track reconstruction of neutron-induced recoil protons in fluorescent nuclear track detectors (FNTDs). (September 2020) - Stabilini, A.; Akselrod, M.S.; Fomenko, V.; Greilich, S.; Harrison, J.; Yukihara, E.G.
Abstract: This work presents the analysis of the images acquired by 3D scans of Fluorescence Nuclear Track Detector (FNTD)-based neutron dosimeters irradiated with fast neutrons. The objective is to demonstrate the feasibility of 3D track-spot detection and trajectories reconstruction of recoil protons, offering a robust δ-ray filtering, and investigate if this analysis provides useful information on the exposure conditions, compared to the currently implemented single-layer analysis. The FNTD crystal volume was scanned with a confocal laser scanning microscope to obtain stacked images. The images were processed to detect the foreground track-spots, which were linked using a particle tracking software. We performed a statistical analysis of the recoil-protons reconstructed trajectories. The analyzed data show that it is possible to distinguish neutron spectra having different energies by analyzing the ranges of the detected particles. Moreover, we demonstrate that the incidence of radiation angle can be determined in directional fields. For a reliable detector evaluation, however, better statistics obtained by scanning larger area of the FNTD crystal is needed. Highlights: FNTDs exposed to fast neutrons were scanned in 3D to acquire recoil protons track-spots. Recoil protons trajectories were reconstructed from the track-spots. The statistical analysis of the reconstructed tracks can determine the angle of exposure. The ranges of the reconstructed tracks give information on the energy of the neutron field.